2019
DOI: 10.1590/s0100-83582019370100068
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wheat Plants to Combinations of Herbicides with Insecticides and Fungicides

Abstract: The combination of herbicides and other pesticides can influence weed and crop management. This study aimed to evaluate the response of the combination of different herbicides with insecticides or fungicides of different chemical groups on the development and yield of wheat grains of the cultivar ORS Vintecinco. The experimental design was a randomized block design with three replications. The experiment consisted of 33 treatments, as follows: control without application and application of the herbicides 2,4-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…In a previous study, an average increment of 3% was observed in the thousand-grain weight of barley cultivars MN610 and Crioula treated with the herbicide 2,4-D amine, compared to the witness without application of the product (Galon et al, 2014). Viecelli et al (2019) found no change in the thousand-grain weight of wheat when treated with 2,4-D amine at the third tiller emission stage.…”
Section: Resultsmentioning
confidence: 81%
“…In a previous study, an average increment of 3% was observed in the thousand-grain weight of barley cultivars MN610 and Crioula treated with the herbicide 2,4-D amine, compared to the witness without application of the product (Galon et al, 2014). Viecelli et al (2019) found no change in the thousand-grain weight of wheat when treated with 2,4-D amine at the third tiller emission stage.…”
Section: Resultsmentioning
confidence: 81%
“…Segundo Velini et al (1995) esses valores são considerados baixos. Viecelli et al (2019) observaram que a máxima fitotoxicidade ocasionada pelo 2,4-D na cultivar de trigo OR Vintecinco foi de 14,24%, sendo que a cultura conseguiu se recuperar dessa injúria, no decorrer das avaliações. O 2,4-D amina causou injúria máxima de 2,9% quando aplicado em pós-emergência do trigo e sua estatura não reduziu quando comparado a testemunha sem aplicação (Soltani et al, 2006).…”
Section: Resultsunclassified
“…In addition to these factors, applying herbicides combined with insecticides or fungicides may exacerbate any injury. Viecelli et al (2019) observed a decrease in wheat plant yield with herbicide application, for 2,4-D and pyroxsulam, in combination with the insecticide chlorpyrifos, in relation to the application of herbicides alone. Hooker et al (2018) observed that herbicides, including 2,4-D, exhibited an increase in potential injury and a decrease in wheat yield when applied in combination with insecticides and/or fungicides.…”
Section: Herbicidementioning
confidence: 89%
“…The herbicides diclofop and iodosulfuron are selective for wheat, even under the water stress conditions observed in the experiment 1, while 2,4-D, clodinafop, saflufenacil, pyroxsulam and triclopyr were selective in the experiment 2. In other studies, selectivity was determined for 2,4-D (Hooker et al 2018, Viecelli et al 2019, Crose et al 2020, clodinafop (Zahid et al 2013), saflufenacil (Piasecki et al 2017), pyroxsulam (Viecelli et al 2019, diclofop (Singh et al 2020) and iodosulfuron (Piasecki et al 2017).…”
Section: Herbicidementioning
confidence: 99%